Test purchase of new synthetic tryptamines via the Internet: Identity check by GC-MS and separation by HPLC - Magdalena Taschwer, Edith Ebner, Martin G Schmid (Journal of Applied Pharmaceutical Science, 2016)
Over the past few years, a continuous alteration of the recreational drug market took place. Among other novel psychoactive drugs, new synthetic tryptamine derivatives appeared on the market. These compounds are mainly traded via the Internet, which has become an important marketplace for the sale of recreational drugs. The goal of our research was to check, if 13 new synthetic tryptamines obtained by test purchase via different online vendors meet the promised identity. Analysis was performed by GC-MS, using a common 30 m HP-5MS capillary column as stationary phase. Subsequently, a simple HPLC method for the separation of these tryptamines was developed. Therefore, the aim was to establish a method to separate a broad spectrum of trypamines simultaneously within short time. Measurements were performed by a LiChrospher® RP-18e column and a mobile phase consisting of 0.1% triethylammonium acetate buffer, methanol and acetonitrile. Both presented methods were found to be suitable for the identification as well as separation of tryptamines as the analysis times were short and the selectivity sufficient. Moreover, enantioseparation of 3 chiral tryptamine derivatives purchased via the Internet by HPLC-UV and an Astec® Cyclobond I™ 2000 as CSP was performed. All of them were sold as racemic mixtures.
Keywords: Tryptamines, Legal highs, Novel psychoactive drugs, HPLC, GC-MS.